Biodiesel Synthesis From Cucumis melo Var. agrestis Seed Oil: Toward Non-food Biomass Biorefineries - Ameen, Maria; Zafar, Muhammad; Nizami, Abdul-Sattar; Ahmad, Mushtaq; Munir, Mamoona; Sultana, Shazia; Usma, Anwar; Rehan, Mohammad (Frontiers in Energy Research, 2022)
This study aims to examine the potential of non-edible seed oil (Cucumis melo var. agrestis, seed oil content 29.1 %, FFA 0.64 mm KOH/g) for biodiesel production via nanocatalyst. Catalyst was characterized using X-ray diffraction spectroscopy (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron microscopy (SEM), and Energy Dispersive X-ray spectroscopy (EDX). The maximum biodiesel yield (93 %) attained under optimized conditions i.e., 9:1 methanol to oil ratio, 2 wt. % catalyst (MgO) at 60 ℃. The synthesized biodiesel yield was optimized through response surface technology via Central Composite Design (CCD). Biodiesel was characterized by advanced analytical techniques such as Gas Chromatography and Mass Spectroscopy, FTIR, and Nuclear Magnetic Resonance (NMR). Fuel properties of synthesized biodiesel, including density (0.800 kg/L), K. viscosity @ 40 °C (4.23 cSt), cloud point -12 ℃, pour point -7 ℃, sulphur content (0.0001 %), flash point (73.5 ℃), total acid no (0.167 mg KOH/g) were found in lines with international standard of American Society of Testing Materials (ASTM). Cucumis melo var. agrestic seed oil, and nano MgO catalyst appeared as economical, sustainable, and feasible candidates to overcome global energy glitches and environmental issues.